Use of creatine on trength training - a systematic review - Vargas, Adriana (2012)
Objective: To verify, through systematic review, the ergogenic effects of creatine supplementation on strength training. A systematic review on original national and international articles from the last ten years was performed. Twenty six articles were analyzed, 8 were reviews and 18 were field articles that were researched on health related magazines. The analyzed studies are experimental with creatine and placebo and the sample was mostly selected among physically active individuals of both genders. According to the analyzed articles, most studies showed that creatine supplementation presented positive results on the increase of maximum strength and lean body mass, decreasing fatigue and improving physical performance of athletes. Body weight increase may be associated with the osmo-regulator capacity creatine presents, causing water influx within the cell. The used dose on most studies was 20g of creatine divided in four doses during the first five days, and 2g and 5g per day for the remaining of the study. However, these results were only found on high intensity and short-term exercises over long-term training. The studies that did not present results were performed on short-term tests. The results found on the studies suggest creatine supplementation, that when used correctly may lead to significant gains on athletes’ performance during high intensity and short-term exercises over long-term trainings.